Characterization of Aspergillus fumigatus secretome during sublethal infection of Galleria mellonella larvae - Curtis, Aaron; Dobes, Pavel; Marciniak, Jacek; Hurychova, Jana; Hyrsl, Pavel; Kavanagh, Kevin (Journal of medical microbiology, 2024)
Introduction. The fungal pathogen Aspergillus fumigatus can induce prolonged colonization of the lungs of susceptible patients, resulting in conditions such as allergic bronchopulmonary aspergillosis and chronic pulmonary aspergillosis.Hypothesis. Analysis of the A. fumigatus secretome released during sub-lethal infection of G. mellonella larvae may give an insight into products released during prolonged human colonisation.Methodology. Galleria mellonella larvae were infected with A. fumigatus, and the metabolism of host carbohydrate and proteins and production of fungal virulence factors were analysed. Label-free qualitative proteomic analysis was performed to identify fungal proteins in larvae at 96 hours post-infection and also to identify changes in the Galleria proteome as a result of infection.Results. Infected larvae demonstrated increasing concentrations of gliotoxin and siderophore and displayed reduced amounts of haemolymph carbohydrate and protein. Fungal proteins (399) were detected by qualitative proteomic analysis in cell-free haemolymph at 96 hours and could be categorized into seven groups, including virulence (n = 25), stress response (n = 34), DNA repair and replication (n = 39), translation (n = 22), metabolism (n = 42), released intracellular (n = 28) and cellular development and cell cycle (n = 53). Analysis of the Gallerial proteome at 96 hours post-infection revealed changes in the abundance of proteins associated with immune function, metabolism, cellular structure, insect development, transcription/translation and detoxification.Conclusion. Characterizing the impact of the fungal secretome on the host may provide an insight into how A. fumigatus damages tissue and suppresses the immune response during long-term pulmonary colonization.
Keywords: Secretome; sekretom; Galleria mellonella; gliotoxin; Virulence Factors; můry; virulence; proteom; Aspergillus; hemolymfa; Fungal Proteins; Aspergillosis; proteomics; Virulence; aspergilóza; Aspergillus fumigatus; faktory virulence; proteomika; larva; Animals; zvířata; Larva; Proteomics; Hemolymph; Proteome; fungální proteiny; Moths; fungal–host interactions